Preliminary Methodology for the Integration of Lean Construction, BIM and Virtual Reality in the Planning Phase of Structural Intervention in Heritage Structures - Brioso X. (2019)
The development of the LPDS methodology component was funded by the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica del Perú (CONCYTEC from its acronym in Spanish), according to the Convenio de Gestión N° 232-2015-FONDECYT. The support to the first two authors is greatly appreciated. The team would like to thank Dr. S. Gibson (University of the Holy Land), the head archaeologist working at the SJH for inviting the third and fourth author to work in this project. The third and fourth author would like to thank the Armenian Patriarchate and Father Asbed at the Church of the Nativity convent for the access to the site. Engineer Issa Juha, graduate students Peter Hubbard and Mauricio Gonzales, and Dr. Steve Patterson provided support to the team during the experimental campaign. The opinions presented herein do not necessarily reflect the opinions of CONCYTEC, or of these individuals and their organizations.